A Neglected Animal Model for a Neglected Disease: Guinea Pigs and the Search for an Improved Animal Model for Human Brucellosis - Hensel, Martha E.; Arenas-Gamboa, Angela M. (Frontiers in Microbiology, 2018)
Brucellosis is a bacterial disease caused by species of the Brucella genus and affects a wide variety of domestic and wildlife species and is also an important zoonosis. The global burden of disease is difficult to assess but Brucella spp. have a worldwide distribution and are endemic in the Middle East, Africa, South America, and Asia. The clinical signs of fever and malaise are nonspecific, and the available serological diagnostic tests lack a high degree specificity in endemic regions compared to other important public health diseases such as malaria. A better understanding of the pathogenesis of brucellosis through discoveries in animal models could lead to improved diagnostics and potentially a vaccine for human use. Mouse models have played an important role in elucidating the pathogenesis but do not replicate key features of the disease such as fever. Guinea pigs were instrumental in exploring the pathogenesis of brucellosis in the early nineteenth century and could offer an improvement on the mouse model as a model for human brucellosis.